(untitled) (Jurnal Anestesi Perioperatif, 2020)
Malnutrisi merupakan masalah penting pada pasien sepsis karena memperburuk outcome akibat penyembuhan luka terganggu, menurunkan fungsi imun, risiko infeksi tinggi, kelemahan otot sehingga weaning ventilator mekanik lebih sulit, meningkatkan lama tinggal dan biaya tinggi di unit perawatan intensif serta peningkatan mortalitas. Skrining risiko nutrisi saat pasien masuk unit perawatan intensif dengan modified NUTRIC score dapat mengidentifikasi kelompok risiko nutrisi tinggi atau risiko rendah. Penelitian kohort retrospektif untuk mengetahui korelasi antara modified NUTRIC score dengan mortalitas pada pasien sepsis yang dirawat dari Januariâ€’Desember 2018 di RSUP Dr. Mohammad Hoesin Palembang. Jumlah sampel 100 orang, dibagi 2 kelompok berdasarkan mortalitas, kemudian dilakukan pengukuran modified NUTRIC score yang terdiri dari usia, skor APACHE II, skor SOFA, lama rawat sebelum masuk perawatan intensif, dan jumlah komorbid. Modified NUTRIC score memiliki nilai 0â€’9. Hasil analisis ROC curve modified NUTRIC score dengan mortalitas didapatkan sensitiftas sebesar 96%, spesifisitas 71%, nilai area under the curve (AUC) 0,916 dengan nilai cut off >4. Terdapat korelasi antara modified NUTRIC score dengan mortalitas dalam 28 hari pasien sepsis dengan koefisien korelasi (r)=0,716 dan nilai p=0,0001. Correlation of Modified Nutric Score with 28-Day Mortality in Sepsis Patients at Intensive Care Unit of Dr. Mohammad Hoesin General Hospital Palembang Malnutrition is an essential problem to septic patients because it worsens the outcome due to impaired wound healing, decreases immune function, high risk of infection, and muscle weakness so that mechanical ventilator weaning is more complicated. Also, it increases the patient length of stay and costs in the intensive care unit and increases mortality. Nutrition risk screening on patients’ admission to the intensive care unit with modified NUTRIC score can identify groups of high nutritional risk or low risk. The retrospective cohort study aimed to determine the correlation between modified NUTRIC score and mortality in sepsis patients treated from January-December 2018 at dr. Mohammad Hoesin General Hospital Palembang. The total sample of 100 people was divided into 2 groups based on mortality then measured with modified NUTRIC score consisting of age, APACHE II score, SOFA score, length of stay before admission to the intensive care, and the number of comorbid based on data from medical records. Modified NUTRIC score has a value of 0â€’9. The ROC curve modified NUTRIC score with mortality was 96% sensitivity, 71% specificity, area under curve (AUC) value 0.916 with a cut-off value >4. There is a correlation between the modified NUTRIC score and mortality in 28 days in sepsis patients in the Intensive Care Unit of Dr. Mohammad Hoesin General Hospital Palembang with a correlation coefficient (r) = 0,716 and p value <0,05.